Seasonal Variation of Edaphic Features of Madhupur Sal Forest, Bangladesh - Hoque, Ahmed Emdadul; Nazrul-Islam, A K. M.; Imamul Huq, S. M. (Ecoprint: An International Journal of Ecology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Seven stands were selected in different areas of the Madhupur Sal (Shorea robusta) forest to study the seasonal variation of available nutrients in soils. Soil samples were collected after every two months at two depths (top soil 0-10 cm and 10-20 cm) and their physicochemical properties were determined. The percentage of soil moisture was found to vary in different stands and pH values of soil ranged from 4.60 to 6.28. Seasonal fluctuation of electrical conductivity was observed. An increasing trend of sodium accumulation was found in both top and sub-soil layers at all the stands. The concentration of potassium also showed a decreasing tendency in both layers. The exchangeable calcium and magnesium contents did not show significant (pH 0.05) seasonal variation. The high values of manganese and iron were confined to top soil and values decreased down the profile. Key words: Shorea robusta, soil, physico-chemical characteristics, seasonal variation. doi: 10.3126/eco.v15i0.1936 ECOPRINT 15: 7-14, 2008